Retirement Reforms: Occupational Strain and Health - Dayaram, Kantha; McGuire, A. (WILEY, 2019)
A concurrent increase in the demand for state age pensions and health care has led to reforms in delaying retirement. We employ thirteen waves of longitudinal data to examine the mental and physical health effects of Australian men and women at “early” and “traditional” retirement. We use before and after propensity score matching (PSM) estimates between treatment and control groups of retired and not retired individuals aged 60 and 65 years. The results indicate a negative health effect according to occupational strain for both genders but a positive mental health effect for retirees with access to self-funded retirement.